Anthropometric profiling of elite junior and senior Australian football players - Veale, J. P.; Pearce, A.; Buttifant, D. C.; Carlson, J. S. (International Journal of Sports Physiology and Performance, 2010)
Purpose: Body structure and physical development must be addressed when preparing junior athletes for their first season in a senior competition. The aim of this preliminary study was to measure the extent of the assumption that final year junior Australian Football (AF) athletes are at a physical mismatch to their senior counterparts. Methods: Twenty-one male participants (17.71 ± 0.27 y) were recruited from one state based elite junior AF competition and forty-one male participants (22.80 ± 4.24 y) were recruited from one club competing in the senior elite Australian Football League (AFL), who were subsequently divided into two groups; professional rookies aged 18-20 y (19.44 ± 0.70 y; n = 18) and professional seniors aged 21+ y (25.43± 3.98 y; n = 23). Dual energy X-ray absorptiometry (DEXA) scans of all participants were completed. Results: Despite being an average 6.0% and 6.1% lighter in total weight and lean mass respectively, no significant difference was found between the elite junior athletes and their professional AFL rookie counterparts. However, significant differences were demonstrated in comparison with the professional AFL senior athletes (P < .01). Both professional AFL groups demonstrated greater than 0.3 kg total bone mineral content (BMC) than the elite junior athletes (P < .01) and significantly greater segmental BMC and bone mineral density (BMD) results (P < .05). Conclusion: While the results identify the differences in body composition of the elite junior athletes, development in a linear fashion is noted, providing useful information for the creation of age appropriate expectations and training programs.